Facts and Fallacies in the Debate on Glyphosate Toxicity - Mesnage, Robin; Antoniou, Michael N. (Frontiers in Public Health, 2017)
The safety profile of the herbicide glyphosate and its commercial formulations is controversial. Reviews have been published by individuals who are consultants and employees of companies commercializing glyphosate-based herbicides in support of glyphosate’s reapproval by regulatory agencies. These authors conclude that glyphosate is safe at levels below regulatory permissible limits. In contrast, reviews conducted by academic scientists independent of industry report toxic effects below regulatory limits, as well as shortcomings of the current regulatory evaluation of risks associated with glyphosate exposures. Two authors in particular (Samsel and Seneff) have published a series of commentaries proposing that long-term exposure to glyphosate is responsible for many chronic diseases (including cancers, diabetes, neuropathies, obesity, asthma, infections, osteoporosis, infertility and birth defects). The aim of this review is to examine the evidential basis for these claimed negative health effects and the mechanisms that are alleged to be at their basis. We found that these authors inappropriately employ a deductive reasoning approach based on syllogism. We found that their conclusions are not supported by the available scientific evidence. Thus the mechanisms and vast range of conditions proposed to result from glyphosate toxicity presented by Samsel and Seneff in their commentaries are at best unsubstantiated theories, speculations or simply incorrect. This misrepresentation of glyphosate’s toxicity misleads the public, the scientific community, and regulators. Although evidence exists that glyphosate-based herbicides are toxic below regulatory set safety limits, the arguments of Samsel and Seneff largely serve to distract rather than to give a rational direction to much needed future research investigating the toxicity of these pesticides, especially at levels of ingestion that are typical for human populations.